Ichthyosis-like outcomes of possible atopic dermatitis - Milano, A. (European Journal of Pediatric Dermatology, 2017)
This child remembers the pathogenetic links between ichthyosis vulgaris and atopic dermatitis (AD) justified by the common genetic defect of filaggrin (1, 2). However, this does not facilitate the definition of its eruption. The history of urticaria in the mother, itching, and localization to the elbows are reminiscent of AD. However, the child did not have any previous atopic manifestation. AD is often associated with ichthyosis vulgaris or palmar hyperlinearity and follicular keratosis that remind you of it. In our patient, ichthyosislike manifestations acutely started at the age of 6 years on a previous inflammatory dot-like eruption and regressed in 10 days without recurrence. The lesions of our patient were also reminiscent of acanthosis nigricans and of “dirty neck” of severe chronic atopic dermatitis. However, in our case the lesions were hyperacute and self-healing.